Primary Forest Opening of Different Relief Areas in the Republic of Croatia - Tibor Pentek; Dragutin Pičman; Hrvoje Nevečerel; Kruno Lepoglavec; Ivica Papa; Igor Potočnik (Croatian Journal of Forest Engineering, 2011)
Particularly since its independence, the Republic of Croatia has invested a lot of money into the construction of primary forest roads, and however, there is still a large lack of adequately opened forest areas, and in future this will be the object of further investments aimed at achieving the planned or target (optimal) forest openness (Pentek et al. 2006). According to Pentek (2002) there are five basic variants of the primary traditional openness: existing primary road density, minimally required primary road density, planned primary road density, target primary road density and optimal primary road density. It should be emphasized that the data on the primary openness do not speak much of the quality of spatial distribution of the components of primary forest road infrastructure. So as to better understand the actual value of the primary openness, the primary openness should always be presented paired with the mean distance of timber extraction, or with the mean distance of access to the endangered forest areas, if speak ing about fire protection roads in the karst area. In Croatia, Technical Requirements for Industrial Roads (roads used in agriculture and forestry) of 1989 by the author Šikić et al. are currently applicable. The last two centuries were rich with changes, findings and accomplish ments, which were also reflected in forestry so that the defined technical features of forest roads had to be adapted to the present needs. The proposal was drawn up of the new Technical Requirements for Industrial Roads (Pentek et al. 2007b, Nevečerel 2010)/Tables 2, 3 and 4). The newly proposed Technical Requirements for Industrial Roads are based on gross traffic load during one day and means of long-distance transfer of wood. Forest roads with higher traffic load should be designed and built in accordance with more demanding technical requirements, and after the construction, a more frequent and inten sive maintenance should be provided for them. With the decrease of the traffic load, Technical Requirements become simpler, and maintenance is provided less frequently and requires less work. The newly designed Technical Re uirements provide an objective classification of forest roads and consequently the application of the actually re quired technical features. The research was carried out at the area of 15 Forest Administrations (FA) that make part of the company »Hrvatske {ume« d.o.o. Zagreb. Due to the lack of data, the research has not involved FA Split (Fig. 1). The goal of research was defined as follows: • defining the existing primary road density by FAs, • distributing the whole area of each researched FA into relief area of a specific category and calculating the planned primary road density in 2010 and planned primary road density in 2020 (excluding the lowland area), • calculating the whole length of forest roads that need to be built so as to achieve the planned primary road density in 2010 and planned primary road density in 2020 in individual FAs, • making comparative analysis of financial resources necessary for achieving the planned primary road density in 2010 and planned primary road density in 2020 by applying the current Technical Requirements for Industrial Roads (Šikić et al. 1989) and newly proposed Technical Requirements for Industrial Roads (Pentek et al. 2007b, Nevečerel 2010). In the total forest area managed by »Hrvatske šume» d.o.o. Zagreb (1,442.14 ha), the lowland area accounts for 322.32 ha (22.35%), the hilly area for 282.56 ha (19.59%), the mountainous area for 497.83 ha (34.52%) and karst area for 339.43 ha (23.54%). Only three FAs are situated within one relief category (FA Vinkovci in lowland area, FA Ogulin in mountainous area and FA Buzet in karst area). The areas managed by other FAs spread in two or three relief areas (Fig. 2). Although the year 2010 is over, forest openness planned for that year (Table 1) has not been achieved in any FA in the whole management area. In FA Karlovac (lowland) and in FA Delnice and Senj (karst) the planned primary road density in 2010 was exceeded. In lowland area, the average primary road density is 8.85 m/ha, in hilly area it is 11.26 m/ha, in mountainous area it is 15.64 m/ha and in karst area it is 7.63 m/ha. (Table 5). According to the categorization of relief areas and total area of each FA, the planned primary road density in 2010 and in 2020 was calculated. For both variants of the planned primary road density, the length of forest roads was determined that needed to be built by the end of the planned period. The results are shown in Table 6 and 7. The largest volume of work in building new forest roads by the end of the planed period 2010 will be required in FA Gospi} (2,529.04 km). According to the analysis based on relief areas, in lowland area the construction of most forest roads will be required in FA Vinkovci (590.36 km), in hilly area in FA Sisak (704.66 km), in mountainous area (1,691.35 km) and in karst area (836.50 km) in FA Gospić (Table 6). Table 8 shows the existing and planned primary road density in 2010 and 2020 by FAs, as well as the quantity (length) of forest roads that need to be built by the above said years. Similar data, integrated at the level of relief ar eas, are shown in Table 9. The costs of construction of forest roads in the period 2004–2010 differ considerably, which is not surprising considering the diversity of relief conditions. The lowest cost of construction of forest roads was in the area of FA Koprivnica (139,940.38 HRK/km), and the highest in area of FA Vinkovci (569,814.58 HRK/km). The average price of construction of all forest roads is 292,736.00 HRK/km (Fig. 3). Based on planned costs of construction of forest roads for each relief area (Anon. 2010); lowland area (500,000.00 HRK/km), hilly area (350,000.00 HRK/km), mountainous area (250,000.00 HRK/km) and karst area (225,000.00 HRK/km) and the applicable Technical Requirements for Industrial Roads ([iki} et al. 1989), the total price cost was calculated of all forest roads that need to be built for achieving the planned openness in 2010 and 2020. For achieving the planned primary road density in 2010, at the level of »Hrvatske {ume» d.o.o. Zagreb, ac cording to the applicable Technical Requirements, it is necessary to invest HRK 3,231,211,000 and for achieving the planned primary road density in 2020 (without the lowland relief area) the investment of HRK 3,684,473,750 is required. According to the newly proposed Technical Requirements, due to the construction of forest roads of lower categories, and hence less demanding technical requirements, it is expected that the prices of construction will be lower by approximately 20% (Pentek et al. 2007). Based on the analysis of the existing primary road density by FAs and by relief categories as at Dec. 31 2009, it can be concluded that the planned primary road density has not been achieved in most state forests. What is more, in a considerable part of forests, not even the minimally required primary road density has been achieved; in lowland area in 4 out of 11 FAs, in hilly area in 5 out of 9 FAs, in mountainous area in 6 out of 12 FAs, which has a considerably negative effect on the quality, efficiency and rationality of management of these insufficiently opened forests. Road density is considerably different in the same relief areas that can be easily compared. In future, when plan ning investments into construction and development of the primary forest road infrastructure, attention should be focused on priorities in directing financial resources into forest areas with poor road density, until balance of the density of forest road network is achieved at the level of the relief area. The values of the planned road density by relief areas should be reviewed and if necessary redefined, taking into consideration all factors affecting the calculation of the optimal (best possible) openness of a specific relief area. Some thought should also be given to extending the time limit in which efforts will be made to achieve the planned values of density of primary forest road infrastructure taking into consideration the objective financial, profes sional and infrastructural capacitates. By an average annual intensity of building forest roads, based on data from 2004 to 2010 (approximately 228 km/y), it would take 44 years to achieve the road density planned for 2010, and 59 years to achieve the road density planned for 2020. Rationalization of financial resources at the level of an individual forest road, and even at the level of a manage ment unit, may not be so significant by the application of the newly proposed Technical Requirements for Indus trial Roads. If, however, the planned and existing primary road density of all forests in the Republic of Croatia is taken into consideration, on one hand, and if the difference in the price of construction and maintenance of different categories of forest roads in similar stand conditions is taken into account, on the other hand, then significant fi nancial resources are in question. The data on the planned primary road density are defined for larger relief areas and they are used as guidelines in primary forest opening. For an accurate calculation of the target (optimal) openness of individual management units, all stand, habitat and other influencing factors of a specific area should be taken into account. Further to the above, deviations will occur from the target (optimal) density of the primary forest road infrastructure on smaller areas (management units), but in acceptable, positive or negative intervals.